Serologic survey in a chamois population of Abruzzo - Leonardo Gentile; Franco Mari; Giusy Cardeti; Gladia Macrì (Hystrix, 2000)
Abstract As part of the Abruzzo National Park wildlife health management program, serum samples from 62 free-living and captive Abruzzo chamois, Rupicapra (pyrenaica) ornata , were tested to estimate antibody presence to some pathogenous agents. The serum, drawn during chemical immobilisations for introductions or population study programs, were tested for: bovine herpes virus 1 (BHV-1), parainfluenza virus (PI3), pesti virus , foot and mouth disease virus (FMD) type O-A-C, bovine leukemia virus (BLV), ovicaprini lentivirus , encephalomyocarditis virus (EMCV), S-phase brucellae , leptospira interrogans , mycobacterium paratuberculosis , chlamydia psittaci , coxiella burnetii , rickettsia mooseri and conori and toxoplasrna gondii . Twenty-three subjects were found positive to BHV-1 (7/62), pestivirus (6/62), EMCV (8/62), leptospira (5/62) and toxoplasma (4/62). Results did not indicate any active infection but only contact with some pathogenic agents.